2015
DOI: 10.1007/s10509-015-2505-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear effects on radiation propagation around a charged compact object

Abstract: The propagation of non-linear electromagnetic waves is carefully analyzed on a curved spacetime created by static spherically symmetric mass and charge distribution. We compute how non-linear electrodynamics affects the geodesic deviation and the redshift of photons propagating near this massive charged object. In the first order approximation, the effects of electromagnetic self-interaction can be distinguished from the usual Reissner-Nordström terms. In the particular case of Euler-Heisenberg effective Lagra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In figure (12) it can be observed that z massless < z ph < z RN , when we consider z redshift in function of q/q c where q c = M.…”
Section: Born-infeld Black Holementioning
confidence: 97%
See 1 more Smart Citation
“…In figure (12) it can be observed that z massless < z ph < z RN , when we consider z redshift in function of q/q c where q c = M.…”
Section: Born-infeld Black Holementioning
confidence: 97%
“…Also in [12], the non-linear electrodynamics effects on the geodesic deviation and the redshift of photons propagating near spherically symmetric mass and charge distributions are analyzed up to the first-order considering the effective metric.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear counterpart of the Maxwell stress tensor causes to deviate the photon geodesics where the photons do not move along the null geodesics. Usually one use an effective metric to study gravitational lensing of the light rays moving on such a charged black holes metric [41][42][43][44]. In the following section we seek effective metric of the ABG black hole for photon trajectories.…”
Section: Abg Space Timementioning
confidence: 99%
“…Furthermore we should point that the nonsingular charged black holes obtained from NEM models in curved space times cause that the photons do not move along null geodesics. As an applicable approach we must be obtain corresponding effective metric for geodesics of moving photons [42][43][44][45] and so study their gravitational lensing. The black hole electric charge has also important effects on final state of the Hawking radiation and switching off effects of a quantum evaporating black hole (see for instance [46]).…”
Section: Introductionmentioning
confidence: 99%
“…Logarithmic and Exponential electrodynamics [6][7][8][9] -and the NLED became a class of electromagnetic theories [10]. This class of theories has applications in several branches of physics being particularly interesting in systems where the NLED are minimally coupled with gravitation as in the cases of charged black holes [11][12][13][14][15][16][17] and cosmology [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%